TRANSITIONAL JUSTICE AND VICTIMS’ RIGHTS (ESMAT Magazine, 2026)
This research analyzes transitional justice with regard to the rights of victims. It also examines alternative mechanisms to criminal justice and highlights the importance of truth commissions, recognizing the significant role these elements play in processes of reparation. In this context, transitional processes encompass different legal, political, and social mechanisms. Therefore, the analysis does not focus solely on the criminal prosecution of those responsible for the acts, but also addresses the rights of victims, which must be fulfilled through mechanisms that complement judicial processes, whether at the national or international level. This approach is particularly relevant in situations involving armed conflicts and massive and systematic violations of human rights. Furthermore, the study draws upon the theory of distributive justice, the contractualist tradition associated with Aristotle, and the more recent neocontractualist perspective represented by John Rawls in A Theory of Justice (1971). Within this transitional framework, the research questions whether it is possible to resort to the distribution of justice as a bridge to transitional justice, and whether one is sufficient without the other, or whether transitional justice would be more viable without resorting to contractualist theories.
Keywords: transitional justice; victims’ rights; human rights